Efficient and Selective Electroreduction of CO2 to HCOOH over Bismuth‐Based Bromide Perovskites in Acidic Electrolytes. Issue 58 (23rd August 2022) - Wang, Yan; Wang, Chun; Wei, Yi; Wei, Fang; Kong, Lichun; Feng, Jiuju; Lu, Ji‐Qing; Zhou, Xiaocheng; Yang, Fa
Abstract: Metal halide perovskites, primarily used as optoelectronic devices, have not been applied for electrochemical conversion due to their insufficient stability in moisture. Herein, two bismuth‐based perovskites are introduced as novel electrocatalysts to convert CO2 into HCOOH in aqueous acidic media (pH 2.5), exhibiting a high Faradaic efficiency for HCOOH of >80 % in a wide potential range from −0.75 to −1.25 V. Their structural evolution against water was dynamically monitored by in situ spectra. Theoretical calculations further reveal that the formation of intermediate OCHO* on bismuth sites of Cs3 Bi2 Br9 (111) play a pivotal role toward HCOOH production, which has a lower energy barrier than that on Cs2 AgBiBr6 (001) surfaces. Significantly, CO2 reacts with protons instead of water which can enhance CO2 reduction rate and suppress hydrogen evolution by avoiding carbonate formation in acidic electrolytes. This work paves the way for the extensive investigation of halide perovskites in aqueous systems. Abstract : CO2 reduction : Bismuth‐based perovskites are utilized for CO2 RR into formic acid in strong acid for the first time. The ingenious use of acidic electrolyte not only helps to stabilize the perovskite phase, but also enhances CO2 reduction rate, maintains a high OCHO* intermediate coverage and suppresses HER by avoiding the OH − and carbonate formation, addressing the "alkalinity problem" in CO2 RR.